PENGARUH LATIHAN KERJA TERHADAP VOLUME LIMBAH EKSPLOITASI - Marolop Sinaga; Sampe Radja S; Maman Mansyur (Pusat Penelitian dan Pengembangan Hasil Hutan, 1984)
An investigation of felling waste was carried out at three forest enterproses in North Sumatera. In each forest enterprise, the operation weretrained before data collection was conducted.The result reveals that training has significant effect on reducing the volume of felling waste. The average felling waste before and after training are respectively 0.705 m3/ tree and 0.185 m3/tree.It is therefore recommended that operator needs to be trained before.